STRATEGI KOMUNIKASI PENYULUH AGAMA ISLAM FUNGSIONAL DALAM MEMBERIKAN BIMBINGAN DAN PENYULUHAN KEPADA PESERTA KURSUS PRANIKAH (Studi Kasus di KUA Kecamatan Cilaku, Kabupaten Cianjur) - Dedi Nasrudin (El-Ghiroh : Jurnal Studi Keislaman, 2018)
Pre-Marriage course is an activity of giving a briefing or marriage counseling to peoples who want to marry or for the bride candidates. Pre-Marriage courses are important for bonding and building marriages to be stronger and more solid. The Functional Islamic Counselor of Sub-district can and usually be used as one of the speakers in pre-marriage course activity. In this case, including the Functional Islamic Counselor of Sub-district Cilaku. The purpose of this research is to know the communication strategy in delivery of the material, the use of method, the evaluation form, and the constraints of communication strategyof the functional of Islam religion of Cilaku sub-district in the pre-marriage course activity at the Office of Religious Affairs of Cilaku sub-district.